Truyol y Serra's doctrines of international law - Kolb, Robert, 1967- (Edward Elgar Publishing, 2018)
Inspired by Antonio Truyol y Serra's classic work, Doctrines sur le fondement du Droit des gens, this book offers a fully revised and updated examination and discussion of the various doctrines forming the foundations of international law. It offers an accessible insight into the theoretical background of the various legal constructions that characterize the relationship between both international and national legal orders. Written in a clear style, the book's structured chapters provide a comprehensive analysis of the various foundations of obligation in international law: natural law, positivism and sociologism. Through this study, Robert Kolb illustrates how international law has been conceived and shaped over time in relation to its evolving historical and legal-political environment. Split into seven substantive parts, this text is one of the most detailed expositions of the doctrines of international law in the English language to date. Astute and engaging, Robert Kolb's take on Truyol y Serra's Doctrines sur le fondement du Droit des gens will appeal to students and scholars of international law, as well as to practitioners interested in gaining a further grounding with regards to the basis of obligation in international law.